1997
DOI: 10.1007/s001340050358
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant nebulisation: safety, efficiency and influence on surface lowering properties and biochemical composition

Abstract: The MiniNEB nebulised surfactant safely in a neonatal ventilator setting with respect to airway pressures. The efficiency of nebulisation is low: the majority of the surfactant aerosol is deposited in the expiratory tubing. The surfactant composition and function is not altered by nebulisation. Therefore the nebulisation of surfactant is feasible, but efforts should be made to improve the efficiency of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Nebulized surfactant has been shown to be safer and less harmful compared with intratracheal liquid instillation. A study performed by Dijk et al (31) has shown that the partial pressure of oxygen in arterial blood increased quickly after instillation compared with a gradual increase during nebulization of Alveofact Ò over 120 minutes. However, there were also rapid decreases in the mean arterial blood pressure and cerebral blood flow after liquid instillation by 22% and 64%, respectively, whereas there was no change in the mean arterial blood pressure and only 31% gradual drop of cerebral blood flow after nebulization.…”
Section: Discussionmentioning
confidence: 99%
“…Nebulized surfactant has been shown to be safer and less harmful compared with intratracheal liquid instillation. A study performed by Dijk et al (31) has shown that the partial pressure of oxygen in arterial blood increased quickly after instillation compared with a gradual increase during nebulization of Alveofact Ò over 120 minutes. However, there were also rapid decreases in the mean arterial blood pressure and cerebral blood flow after liquid instillation by 22% and 64%, respectively, whereas there was no change in the mean arterial blood pressure and only 31% gradual drop of cerebral blood flow after nebulization.…”
Section: Discussionmentioning
confidence: 99%
“…16 Dijk et al studied 9 infants and reported efficacy rates of <10% with surfactant nebulization and noted that most aerosolized surfactant was expired and did not reach the lungs. 17 More recent RCTs have reported minimal benefits at best. 18,19 Berggren et al conducted an RCT involving 32 infants (16 treated with nebulized surfactant and 16 who did not receive surfactant) and reported no significant difference in the requirement of mechanical ventilation or the incidence of BPD ( P > .05).…”
Section: Discussionmentioning
confidence: 99%
“…23 Efficacy rates of <10% have been attributed to the large particle size of the surfactant and the small airways of preterm neonates. 16-18,20,21 …”
Section: Discussionmentioning
confidence: 99%
“…In the SURFNEB group, surfactant was nebulised using the Miniheart low-flow volume medication nebuliser (MiniNEB, Vortran Medical Technology, Sacramento, Calif., USA) tested earlier during in vitro experiments [17]. This nebuliser produces an aerosol with particle sizes that enhance a peripheral deposition of the surfactant in the lungs (mass median aerodynamic diameter was 3 mm and 70 % of the particles were between 1 and 5 mm in diameter) [17].…”
Section: Surfactant Treatmentsmentioning
confidence: 99%